Hotel Transylvania [videorecording (DVD)] - Tartakovsky, Genndy, 1970-; Sandler, Adam; Sandler, Adam; Samberg, Andy, 1978-; Gomez, Selena, 1992-; James, Kevin, 1965-; Drescher, Fran; Buscemi, Steve, 1957-; Shannon, Molly, 1964-; Spade, David; Cee-Lo (Musician) (Sony Pictures Home Entertainment, 2013)
The Hotel Transylvania, run by Dracula, is a unique, high-end resort catering only to the finest monsters and their families. Dracula is preparing for an extra special weekend - his daughter Mavis's 118th birthday - when trouble arises: a human has stumbled upon the resort for the first time ever! Even worse: the human has taken a liking to Mavis!